The Impact of Operational Efficiency, Dividend Policy, and Corporate Sustainability On Financial Performance - Juergen Klinsman Daniel Simanjuntak; Rolyana Ferinia; Judith Tagal Gallena Sinaga (Interdisciplinary Social Studies, 2025)
In contemporary business practice, companies have become increasingly aware of the need to enhance financial performance to provide optimal dividends to investors while simultaneously managing operational costs and demonstrating environmental responsibility through corporate sustainability reports. This study aims to examine the extent to which operational efficiency, dividend policy, and corporate sustainability influence the financial performance of firms. Employing a quantitative research design with a correlational approach, data were analysed using SPSS. Secondary data were collected from 63 companies listed on the Indonesia Stock Exchange (IDX) that report Environmental, Social, and Governance (ESG) scores, alongside their annual reports for the year 2023. The findings indicate that: 1) Operational efficiency does not have a significant effect on financial performance; 2) Dividend policy exerts a positive and significant impact on financial performance; 3) Corporate sustainability does not significantly influence financial performance; and 4) Collectively, operational efficiency, dividend policy, and corporate sustainability significantly affect financial performance. This research focuses on publicly listed companies in Indonesia with ESG scores, highlighting their commitment to environmental, social, and governance factors while concurrently pursuing profitability.